Debt services capital inflows and economic growth in North African countries - Abud, Elmashat Essadq Ali (2014)
The North African countries namely Algeria, Egypt, Mauritania, Morocco and Tunisia rely heavily on external funds for financing its development. Such external funding usually takes the form of external loans. This study advances the argument that the real problem that impedes the process of economic growth is the challenge of inadequate real resources for capital formation, due to high external debt servicing. The mounting debt stocks have discouraged the inflow of foreign capital in the form of Foreign Direct Investment (FDI) for fear of macroeconomic distortions. It is scarcely surprising that high debt-service obligation has not only made North African economies to perform poorly but also to rely heavily on foreign sources of budgetary support, thereby creating an unending cycle of economic crisis. In a nutshell, this study used a simultaneous equations model to test the process of interaction between FDI inflows, external debt service and economic growth. The analysis uses the Three Stage Least Square and panel cointegration test to investigate the relationship between debt service, FDI inflow and other determinants and economic growth. The results showed a negative sign and significant relation between debt service and economic growth. The results also show that FDI inflows play an important role and increased the economic growth. The interaction variables between debt crisis with FDI inflows, debt crisis and domestic saving show a negative effect on economic growth in some countries and a positive effect on economic growth in others. In terms of policy, the governments should promote rational and proper utilization of resources, while trying to get more concession on newly acquired debt inflows. It also indicates that policymakers should act early when choosing to lean against credit booms, before the debt service reaches critical levels.